Expectations, Effectiveness, Trust, and Cooperation: Public Attitudes towards the Israel Police during the COVID-19 Pandemic. (1st November 2020) - Perry, Gali; Jonathan-Zamir, Tal
Abstract: The COVID-19 pandemic significantly affected the work of police agencies worldwide. Within a short period of time, the police were assigned new responsibilities and were required to change their priorities and focus on enforcing unusual emergency orders. These new tasks, as well as the emergency atmosphere and its socio-psychological implications, raise a series of questions about public expectations from and trust in the police during the pandemic period. In this article, we report the views of majority communities in Israel (non-Orthodox Jews), as expressed in a survey carried out in the midst of the pandemic. We find that this population supports police enforcement of the new orders and trusts them to do so with integrity, believes the police have been successful in this arena, and is willing to report violations of emergency regulations. Overall, responses indicate more favourable attitudes towards the police, echoing previous findings on policing emergencies.